(untitled) (Scientific journal of the Fergana State University, 2024)
This study investigates that this crystallization of the Sodium Chloride (NaCl) soluble concentrations in solutions at variable concentrations (0.1%, 0.9%, 1.7%) even now... Controlled laboratory conditions (25°C, 32% relative humidity). These crystallization properties were systematically Being analyzed for research its potential at this early diagnosis nephrolitiaznephrolitiaz (kidney stone disease). This morphology of NaCl crystals has been found during this evaporation process, which is aimed at searching for clear crystallization properties in an interrelated range and this Elasticity for Kidney Stone Formation. The key aspects of this Reading Song are the Crystallization of this Initiative, this Crystal Growth of Kinetics, and the Resulting Crystal Morphologies. Other concentrations at this analysisʼs solutions Charged These are the different crystalline structures of the identity. Analyses Obtained from understanding kidney stone Composition and their formation mechanisms retention important Assessment for importance Disease risk and information therapeutic strategies.